Regional diversity in absorbing the EUfunds supporting transformation and development of agriculture in Poland - Kata, Ryszard; Walenia, Alina (Publishing House of the Wrocław University of Economics, 2009)
The condition of progress in adjusting Polish agriculture to requirements of a modern agricultural market is a modification of the EU aid allocation, too much of which is currently used for consumption and too little for farming improvement. It is essential to perform the evaluation of the agricultural policy, paying special attention to the issue concerning benefits of the current EU fund use model to the modernization of the agricultural structure. The evaluation of this sphere should also include the analysis of spatial allocation of EU funds supporting agriculture development, which is essential in the context of the regional diversity of agriculture and, as a result, the need for stimulation of different development paths for this sector. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 217-227